1996
DOI: 10.1152/jn.1996.75.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral structures participating in motor preparation in humans: a positron emission tomography study

Abstract: 1. Using positron emission tomography and measurement of regional cerebral blood flow (rCBF) as an index of cerebral activity we investigated the central processing of motor preparation in 13 healthy volunteers. 2. We used a motor reaction time paradigm with visual cues as preparatory and response signals. A preparatory stimulus (PS) provided either full, partial, or no information regarding two variables of a forthcoming right finger movement: finger type (index or little finger) and movement direction (abduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
235
3
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(276 citation statements)
references
References 6 publications
37
235
3
1
Order By: Relevance
“…Moreover, a modular organization of internal models of tool manipulation has been recently reported in the cerebellum using fMRI [Imamizu et al, 2003], extending the predictions of the MOSAIC computational model [Haruno et al, 2001;Wolpert and Kawato, 1998] from to the "motor" to the "cognitive" cerebellum. In the present study, we suggest that the vermian cerebellar activation associated with the innervatory pattern stage merely reflects its contribution to movement regulation [Deiber et al, 1996;Jueptner et al, 1996;Kitazawa, 2002] and integration of simple movements into more complex ones [Ramnani et al, 2001;Thach, 1998] during actual movement production. Rothi et al [1991Rothi et al [ , 1997b incorporated in their model the proposal presented by Roy and Square [1985] of a core conceptual, or action semantic, system that involves three kinds of knowledge: knowledge of the functions that tools and objects may serve, knowledge of actions independent of tools, and knowledge about the organization of single actions into sequences.…”
Section: Innervatory Patternsmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, a modular organization of internal models of tool manipulation has been recently reported in the cerebellum using fMRI [Imamizu et al, 2003], extending the predictions of the MOSAIC computational model [Haruno et al, 2001;Wolpert and Kawato, 1998] from to the "motor" to the "cognitive" cerebellum. In the present study, we suggest that the vermian cerebellar activation associated with the innervatory pattern stage merely reflects its contribution to movement regulation [Deiber et al, 1996;Jueptner et al, 1996;Kitazawa, 2002] and integration of simple movements into more complex ones [Ramnani et al, 2001;Thach, 1998] during actual movement production. Rothi et al [1991Rothi et al [ , 1997b incorporated in their model the proposal presented by Roy and Square [1985] of a core conceptual, or action semantic, system that involves three kinds of knowledge: knowledge of the functions that tools and objects may serve, knowledge of actions independent of tools, and knowledge about the organization of single actions into sequences.…”
Section: Innervatory Patternsmentioning
confidence: 58%
“…Notwithstanding, increased cerebellar activation was reported during movement imagination [Decety et al, 1994;Jueptner et al, 1997], preparation [Deiber et al, 1996;Krams et al, 1998], and observation with the aim to imitate [Grèzes et al, , 1999, although the highest activations are usually found during actual movement execution [Deiber et al, 1996;Jueptner et al, 1997;Krams et al, 1998]. Cerebellum plays also a significant role in the early phases of acquisition and planning of motor sequences [Doyon et al, 2002], and is known to participate in a wide variety of cognitive and emotional processes [e.g., see Marien et al, 2001;Middleton and Strick, 1998;Rapoport et al, 2000;Salman, 2002].…”
Section: Innervatory Patternsmentioning
confidence: 99%
“…Neural activity in the SMG has previously been shown to be important for the preparation of limb movements, even when they are not actually executed (Deiber, Ibanez, Sadato & Hallet, 1996;Deiber, Ibanez, Honda, Sadato, Raman & Hallett 1998;Krams, Rushworth, Deiber, Frackowiak & Passingham, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The specific signification of increased gamma band activities observed in the supramarginal gyrus is less clear. The supramarginal gyrus has been associated with temporary storage of phonological material (Paulesu, Frith and Frackowiak, 1993;Cohen et al, 1997;Jonides et al, 1998;Honey, Bullmore and Sharma, 2000), phonological judgements (Romero, Walsh and Papagno, 2006), motor preparation (Deiber et al, 1996), and motor attention (Rushworth, Krams and Passingham, 2001). The present study cannot disambiguate the specific contribution of the supramarginal gyrus to these processes.…”
Section: Discussionmentioning
confidence: 99%